"That's not a man's drink". The construction of gendered identities through stories of wine consumption in Kenya. Issue 3 (8th December 2020) - Clifton, Tim; Clifton, Jonathan; Velikova, Natalia
Abstract : Purpose: The purpose of this paper is to explore how gendered wine-drinker identities are constructed through stories of wine consumption in Kenya. Design/methodology/approach: The data comes from a corpus of 19 in-depth semi-structured interviews collected in Nairobi, Kenya. Taking a narrative approach, this paper uses positioning theory as a fine-grained linguistic methodological tool to analyze stories of gendered wine consumption. Findings: A key finding of the study is that wine consumption can enact, and be enacted by, wider normative societal gendered discourses of what men and women should and, should not, be drinking. In short, in some societies (Kenya being an example here) men drinking wine is subject to the normative gaze of their peers; and if men drink wine, they are not considered "real men." This is so even when chatting up women, in which case male wine-drinkers are ascribed to the subordinate male identities of either the "new man" or the romantic man. However, male wine-drinkers can retain a real man identity if they are wealthy (and powerful) enough not to care what other men think. Practical implications: The study provides new insights for targeting consumers in emerging export markets. Wine companies need to be aware that the purchase drivers in established markets may not be central to consumers in developing markets. In developing markets, wine consumption may be influenced by the normative gaze of peers which enacts, and is enacted by, societal gendered discourses. Crucially, a thorough understanding of consumer behavior leads to a more critical consideration for focused marketing strategies aimed at establishing relationships with customers in developing markets. Originality/value: The study offers an original contribution to the barely existent body of knowledge on wine consumption in sub-Saharan Africa and gendered wine-drinking identity construction. Additionally, from a methodological perspective, no previous study on wine consumption has used a narrative identity approach to the fine-grained linguistic analysis of transcripts of stories elicited during research interviews.